An individualized approach to sustained inflation duration at birth improves outcomes in newborn preterm lambs - Tingay, David G.; Grychtol, Bartłomiej (American journal of physiology. Lung cellular and molecular physiology, 2015)
A sustained first inflation (SI) at birth may aid lung liquid clearance and aeration, but the impact of SI duration relative to the volume-response of the lung is poorly understood. We compared three SI strategies: 1) variable duration defined by attaining volume equilibrium using real-time electrical impedance tomography (EIT; SIplat); 2) 30 s beyond equilibrium (SIlong); 3) short 30-s SI (SI30); and 4) positive pressure ventilation without SI (no-SI) on spatiotemporal aeration and ventilation (EIT), gas exchange, lung mechanics, and regional early markers of injury in preterm lambs. Fifty-nine fetal-instrumented lambs were ventilated for 60 min after applying the allocated first inflation strategy. At study completion molecular and histological markers of lung injury were analyzed. The time to SI volume equilibrium, and resultant volume, were highly variable; mean (SD) 55 (34) s, coefficient of variability 59%. SIplat and SIlong resulted in better lung mechanics, gas exchange and lower ventilator settings than both no-SI and SI30. At 60 min, alveolar-arterial difference in oxygen was a mean (95% confidence interval) 130 (13, 249) higher in SI30 vs. SIlong group (two-way ANOVA). These differences were due to better spatiotemporal aeration and tidal ventilation, although all groups showed redistribution of aeration towards the nondependent lung by 60 min. Histological lung injury scores mirrored spatiotemporal change in aeration and were greatest in SI30 group (P < 0.01, Kruskal-Wallis test). An individualized volume-response approach to SI was effective in optimizing aeration, homogeneous tidal ventilation, and respiratory outcomes, while an inadequate SI duration had no benefit over positive pressure ventilation alone.